A SIMULATED ANNEALING HEURISTIC FOR A CRANE SEQUENCING PROBLEM - McKendall, Alan R; Shang, Jin; Noble, James S.; Klein, Cerry M (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
When maintenance activities during outages at electric power plants are scheduled using project managemenr software, the locations of the resources required to perform the acrivities are determined such that the total distance the resources travel during the outage is minimized. This problem is defined as the dynamic space allocation problem (DSAP). Once the DSAP solution (i.e., assignment of activities and their required resources to workspaces and of idle resources to storage spaces) is obtained, the problem then is to determine the sequence in which the crane moves the resources to their required locations at the beginning of each period (i.e., change in the schedule) such that the total distance the crane travels is mininlized. In this paper, this problem is defined as the crane sequencing problem (CSP), and a simulated annealing heuristic is presented for this problem.